(3eNJUQ GdfYeI GdcHQi Ydi GdYGde HOhdI SjO Hfj BOe Udi Gddg Ydjg hSdes - (3GdngrjnJej GdSYOj Gdecj, CHh GdYHGS, TgGH GdOjf, CMeO Hf eMeO Hf Ydj Hf MLQ, J (B974 (3g`s ((3eMeOs)
(3ChdgG (B:s
(3GdMeO ddg GdPj TQa gPG GdYGde HehdO SjO hdO BOe hced SYhO GdCfHjGA hGdeQSdjf hLejY GdedGFcIs
(3BNQgG (B:s
(3hcGf Udi Gddg Ydjg hSde gh GdhGVY ddMLQ GdCShO aj eMdg Ke deG HdZ Udi Gddg Ydjg hSde CQHYjf SfI CQSdg Gddg JYGdi QMeI ddYGdejf hQShdG Edi cGaI GdNdb CLeYjfs
(3efbhdI ef fSNI GdeDda GdeDQNI SfI (B967(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 1 / 234s
(3eYLe GdeDdajf(B: 1 / 293 (3, (B294s
(3EjVGM Gdecfhf(B: 2 / 661s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs